THE ASSOCIATION OF CARDIOVASCULAR SYSTEM ADAPTATION INDICATORS IN ADOLESCENT FOOTBALL PLAYERS WITH ACE I/D (RS4646994) GENE POLYMORPHISMS - A.A. Ruzieva (Journal of modern medicine, 2026)
Recent research in sports genomics indicates that genes involved in regulating vascular tone, neurohumoral balance, energy metabolism, and myocardial structure significantly influence the adaptation of the cardiovascular system. ACE gene polymorphisms are one of the most studied and clinically significant genetic determinants of cardiovascular adaptation. The angiotensin-converting enzyme (ACE) gene encodes angiotensin II, a potent vasoconstrictor, and the key RAAS enzyme involved in regulating vascular tone, circulating blood volume, and myocardial remodeling. Objective. To assess the association between ECG parameters, which reflect cardiovascular system adaptation, and ACE I/D (rs4646994) gene polymorphisms in adolescent football players. Research materials included 100 adolescent football players who regularly engage in football (MG) and 60 adolescents who participate in sports during physical education classes as part of the school curriculum (CG). Conclusion. The effect of the ACE I/D (rs4646994) gene polymorphism on ECG parameters was less pronounced in the control group (which did not have regular physical exertion) compared to the main group, which demonstrates the modifying role of physical exertion in the realization of genetically determined features of cardiovascular adaptation.